Transformasi Konten Berita Pada Media Digital BUMN Track Dalam Mencapai Bisnis Berkelanjutan (Cakrawala - Jurnal Humaniora, 2024)
Digitalization forces print media to transform into online media so that the number of online media increases. Data from the Press Workers Union (SPS) in 2022, the number of print media will decrease to only 399 media. In the competitive era of digitalization, online media businesses must be sustainable so that the media continues to operate. The previous year there were still 593 print media. The BUMN Track print magazine utilizes digital platform media in delivering news content to build a sustainable business in the digital era. The print magazine BUMN Track, which is published once a month, has been transformed into bumntrack.co.id and BUMN Track TV, whose news content can be seen on YouTube, Instagram, Facebook. Research title: Transformation of BUMN Track News Content in Achieving Sustainable Business. This research uses a qualitative approach to gain an understanding of the reality in the field and conduct qualitative research to explore matters related to content transformation. Research results: The transformation of BUMN Track content into digital media has maintained BUMN Track's credibility in the eyes of readers and clients in the center. The transformation of BUMN Track's news content encourages sustainable business development amidst the decline in the media business. The transformation of BUMN Track content into digital media ensures that BUMN Track's branding as a news media specifically for BUMN is maintained. The transformation of news content into digital media carried out by BUMN Track has encouraged efforts to build a sustainable business.